From Conqueror to Symbol: Early Modern English Representations of Umar ibn Al-Khattab (رضي الله عنه) (Al Basirah, 2025)
While scholarly attention on the representation of Prophet Muhammad ﷺ in early modern English writings has received considerable attention since Nabil Matar’s groundbreaking 1998 study, the companions of the Prophet, particularly Umar ibn Al-Khattabرضي الله عنه, remain underexamined. This paper traces the representations of Umarرضي الله عنه across early modern English texts from 1481 to the mid-seventeenth century, demonstrating that English writers engaged with three distinct representations of Umarرضي الله عنه: as the conqueror of Jerusalem, as the administrator of Islamic territories, and as the symbolic counterpart to Aliرضي الله عنه in sectarian divisions. Through archival analysis using of travel narratives, historical texts, and religious polemics, this paper argues that the emergence of Umarرضي الله عنه in early modern English discourse was inextricably linked to European encounters with the Ottoman and Safavid empires, and that representations of the Prophet’s companions serve as crucial indices for understanding early modern English knowledge production about Islamic civilization. This study employs a mixed-methods approach, combining digital corpus analysis of EEBO resources with close reading of early modern English texts to examine the discursive formation and multilayered representations of Umarرضي الله عنه.Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified.Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies.Participant Consent:  The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.Data Fabrication/Falsification Statement: The author(s) declare that no data have been fabricated, falsified, or manipulated in this study.Copyright: Author(s) retains the Copyright of this article.
Keywords: Early Modern English Literature; Umar ibn al-Khattab (رضي الله عنه); Islamic–European Encounters; Ottoman and Safavid Empires; Representation of Islam in the West